Increasing Aud's Mathematical Logical Intelligence through the Use of Puzzle Pipe Media - Devy Umi Subahiriyah; Sti Hamidahtur Rofi’ah (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2024)
Mathematical, logical intelligence in children is the ability to recognize colours and shapes effectively to improve number management skills and the ability to use logic or common sense. So, mathematical and logical intelligence is one of the intelligences that influence a child's life. Mathematical and logical intelligence has long been favoured and recognized. Many psychometric tests provide extensive space for this intelligence, and it is one of the most vital indicators in assessing students namely It can be said to be intelligent or not intelligent; every PAUD educator stimulates mathematical logic intelligence because the success of this stimulation will have a vast impact on the child's development. After all, almost all life activities cannot be separated from this intelligence. This research uses a case study type of research. Case study research is a direct research method in a natural setting and focuses on events intensively and in detail. Scientific articles are obtained from journals, books, and other similar sources. The location of this research was the Bustanul Ulum Bulugading Play Group, located in the village of Langkap Bangsalsari in Jember. The informants were determined using purpose sampling, namely a sampling technique with specific considerations; in this case, the informant researchers included the school principal, class teachers, guardians and KB Bustanul Ulum Bulugading Bangsalsari Jember students. The data collection technique uses interviews, observation and documentation. Meanwhile, data analysis in this study used the Miles and Huberman data analysis technique. The research results conclude that increasing early childhood mathematical, logical intelligence through pipe puzzle media has been proven influential in introducing mathematical concepts in a concrete and fun way to young children. It can also introduce geometric concepts, develop logical thinking, encourage mathematical reasoning, and stimulate abstract thinking in early childhood. The pipe puzzle medium can also create a pleasant atmosphere and attract children's interest in learning. Therefore, using pipe puzzle media is very helpful for educators at KB Bustanul Ulum Bangsalsari Jember to use as a learning medium.